Efficient Ammonia Electrosynthesis from Nitrate on Strained Ruthenium Nanoclusters - Li, Jie; Zhan, Guangming; Yang, Jianhua; Quan, Fengjiao; Mao, Chengliang; Liu, Yang; Wang, Bo; Lei, Fengcai; Li, Lejing; Chan, Alice W. M; Xu, Liangpang; Shi, Yanbiao; et al. (Journal of the American Chemical Society, 2020)
The limitations of the Haber–Bosch reaction, particularly high-temperature operation, have ignited new interests in low-temperature ammonia-synthesis scenarios. Ambient N2 electroreduction is a compelling alternative but is impeded by a low ammonia production rate (mostly <10 mmol gcat –1 h–1), a small partial current density (<1 mA cm–2), and a high-selectivity hydrogen-evolving side reaction. Herein, we report that room-temperature nitrate electroreduction catalyzed by strained ruthenium nanoclusters generates ammonia at a higher rate (5.56 mol gcat –1 h–1) than the Haber–Bosch process. The primary contributor to such performance is hydrogen radicals, which are generated by suppressing hydrogen–hydrogen dimerization during water splitting enabled by the tensile lattice strains. The radicals expedite nitrate-to-ammonia conversion by hydrogenating intermediates of the rate-limiting steps at lower kinetic barriers. The strained nanostructures can maintain nearly 100% ammonia-evolving selectivity at >120 mA cm–2 current densities for 100 h due to the robust subsurface Ru–O coordination. These findings highlight the potential of nitrate electroreduction in real-world, low-temperature ammonia synthesis.